1997
DOI: 10.1034/j.1399-3054.1997.1010225.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of light in changes in free amino acid and polyamine contents at chilling temperature in maize (Zea mays)

Abstract: 1997. Role of light in changes in free amino acid and polyamine contents at chilling temperature in maize (Zea mays). -Physiol. Plant. 101: 434-438.The effect of irradiance on changes in photosynthesis, free amino acids and polyamines was investigated. Two-week-old maize (Zea mays L.) plants were chilled at 5°C in the light (250 |jmol m~' s~' PAR) or dark. The chlorophyll fluorescence ratio, Fv/Fn,, decreased in the light by ca 50% but did not change in the dark. Similarly to the Fv/Fn,, there was no change in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 14 publications
3
16
0
Order By: Relevance
“…Indeed, a higher activity of adenosine 5¢-phosphosulfate sulfotransferase, the regulatory enzyme of sulfate reduction, was found in maize during lowtemperature stress, resulting in an increased cysteine level (Kocsy et al 1996). Low-temperature stress also induced an increase in glutamate and glycine (Szalai et al 1997). Similar to the results obtained in maize, low temperature increased the rate of cysteine biosynthesis in wheat as shown in the sulfate-labelling experiments presented here.…”
Section: Discussionsupporting
confidence: 78%
“…Indeed, a higher activity of adenosine 5¢-phosphosulfate sulfotransferase, the regulatory enzyme of sulfate reduction, was found in maize during lowtemperature stress, resulting in an increased cysteine level (Kocsy et al 1996). Low-temperature stress also induced an increase in glutamate and glycine (Szalai et al 1997). Similar to the results obtained in maize, low temperature increased the rate of cysteine biosynthesis in wheat as shown in the sulfate-labelling experiments presented here.…”
Section: Discussionsupporting
confidence: 78%
“…Other non-protein amino acids such as GABA and glycine betaine may be detected in the free amino acid pool under cold stress, as well as (Palma et al, 2014;Shelp et al, 2012). Increasing of 13 different amino acids and putrescine has been reported from maize under chilling condition (Janmohammadi et al, 2015;Szalai et al, 1997). In the present work, increasing of Bradford total protein and free amino acids contents was revealed in the s tevia plants treated with 4 °C cold combined with polyamines.…”
Section: Discussionmentioning
confidence: 49%
“…It has been demonstrated that hardening is much less effective in the dark than under normal light conditions (Janda et al, 2014). However, exposure of plants to low temperatures also enhances the level of photoinhibition, which does not only impair the the photosynthetic machinery, but may also modify other stress-related processes (Szalai et al, 1997). Contrary to bread wheat, Szűcs et al (1999) observed that four to six weeks are necessary for the development of adequate cold-hardiness in durum wheat.…”
Section: Discussionmentioning
confidence: 99%